Dynamic Positioning of Underwater Robotic Vehicles with Thruster Dynamics Compensation. (12th September 2013) - Bessa, Wallace M.; Dutra, Max S.; Kreuzer, Edwin
The development of accurate control systems for underwater robotic vehicles relies on the adequate compensation of thruster dynamics. Without compensation, the closed-loop positioning system can exhibit limit cycles. This undesired behaviour may compromise the overall system stability. In this work, a fuzzy sliding-mode compensation scheme is proposed for electrically actuated bladed thrusters, which are commonly employed in the dynamic positioning of underwater vehicles. The boundedness and convergence properties of the tracking error are analytically proven. The numerical results suggest that this approach shows a greatly improved performance when compared with an uncompensated counterpart.